Enhancing students’ performance: Alternative assessment in an ESP course for journalism students - Riestra Carrión, Teresa (2013)
The present study is based on an English for Specific Purposes (ESP) course for journalism students at University Costa Rica (UCR). To design the course assessment as recommended for ESP courses (Dudley Evans & St. John, 1998), the instructors based their decisions on the needs analysis and the assessment type used in UCR journalism major, which consists of projects. Thus, this course assessed students’ performance by means of both traditional and alternative assessment, based on students’ assessment preferences identified in the needs analysis. The aim of this research study was to find out which type of assessment--traditional or alternative--enhanced students’ performance the most. As presumed by the researchers, the results clearly showed that alternative assessment was the type of evaluation that enhanced students’ performance the most, as it is authentic and mirrors students’ real professional contexts.